KEKERASAN DALAM RUMAH TANGGA DALAM PERSPEKTIF HUKUM PIDANA DAN HAK ASASI MANUSIA - Sopian, Muhamad; Gultom, Elfrida Ratnawati (Ensiklopedia Education Review, 2024)
Rights are normative elements inherent in every human being which in their application fall within the scope of the right to equality and the right to freedom related to interactions between individuals and institutions. Rights are something that must be earned. Human rights issues are something that is often talked about and discussed, especially in this reform era. The formulation of the problem is what is meant by a human rights protection institution and how to enforce human rights. The specification of this research is analytical descriptive research. In writing this thesis the author used the Empirical Juridical method. Human rights protection institutions include the National Human Rights Commission (Komnas HAM), Human Rights Court, Legal Aid Institute (LBH), Higher Education Consultation and Legal Aid Bureau. Efforts to uphold human rights can be carried out, among other things, by not disturbing order, maintaining and protecting human dignity, respecting each other's existence, communicating well and politely.Keywords: Domestic Violence, Criminal Law Perspective, Human Rights